A Case Report of Scrupulosity Presenting as Catatonia in a Patient With Both OCD and OCPD. Issue 3 (5th May 2022) - Nikjoo, Arya; Wright, Chela; Kheriaty, Aaron
Abstract : We present the case of a woman in her 40s with a history of hypothyroidism, a differential diagnosis of major depressive disorder with psychotic features versus bipolar I disorder, catatonia, and anorexia nervosa. The patient was admitted to the hospital for poor oral intake, mutism, and social withdrawal. Administration of lorazepam successfully treated these presenting symptoms. However, on subsequent days, she was found to be reading the Bible almost constantly during waking hours, at the expense of engaging in treatment or interacting with others. The patient's history and presentation supported the idea that her hyper-religiosity stemmed not from bipolar disorder or psychosis, as previously thought, but rather from a subtype of obsessive-compulsive disorder referred to as scrupulosity. This report summarizes the characteristics of scrupulosity and discusses this potentially deceptive mimic of more commonly seen conditions.